High-Frequency Variability of the Surface Ocean Properties Off Central Chile During the Upwelling Season - Aguirre, Catalina; Garreaud, René; Belmar, Lucy; Farías, Laura; Ramajo, Laura; Barrera, Facundo (Frontiers in Marine Science, 2021)
The ocean off south-central Chile is subject to seasonal upwelling whose intensity is mainly controlled by the latitudinal migration of the southeast Pacific subtropical anticyclone. During austral spring and summer, the mean flow is equatorward favoring coastal upwelling, but periods of strong southerly winds are intermixed with periods of relaxed southerlies or weak northerly winds (downwelling favorable). This sub-seasonal, high-frequency variability of the coastal winds results in pronounced changes in oceanographic conditions and air-sea heat and gas exchanges, whose quantitative description has been limited by the lack of in-situ monitoring. In this study, high frequency fluctuations of meteorological, oceanographic and biogeochemical near surface variables were analyzed during two consecutive upwelling seasons (2016–17 and 2017–18) using observations from a coastal buoy located in the continental shelf off south-central Chile (36.4°S, 73°W), ∼10 km off the coast. The radiative-driven diel cycle is noticeable in meteorological variables but less pronounced for oceanographic and biogeochemical variables [ocean temperature, nitrate (NO3−), partial pressure of carbon dioxide (pCO2sea), pH, dissolved oxygen (DO)]. Fluorescence, as a proxy of chlorophyll-a, showed diel variations more controlled by biological processes. In the synoptic scale, 23 active upwelling events (strong southerlies, lasting between 2 and 15 days, 6 days in average) were identified, alternated with periods of relaxed southerlies of shorter duration (4.5 days in average). Upwelling events were related to the development of an atmospheric low-level coastal jet in response to an intense along-shore pressure gradient. Physical and biogeochemical surface seawater properties responded to upwelling favorable wind stress with approximately a 12-h lag. During upwelling events, SST, DO and pH decrease, while NO3−, pCO2sea, and air-sea fluxes increases. During the relaxed southerly wind periods, opposite tendencies were observed. The fluorescence response to wind variations is complex and diverse, but in many cases there was a reduction in the phytoplankton biomass during the upwelling events followed by higher values during wind relaxations. The sub-seasonal variability of the coastal ocean characterized here is important for biogeochemical and productivity studies.